Avaliação da estabilidade de agrotóxicos frente às condições de tratamento de água utilizando SPME-GC/MS e ESI/MS - Amauri Geraldo de Souza (2011)
Pesticides, even encouraging the production and preservation of foods, are harmful waste and its detection has required strict control methods. The advancement of analytical technologies have allowed sensitive and selective detection of these substances at trace levels. This paper describes the use of the techniques of gas chromatography-mass spectrometry (GC/MS) and mass spectrometry with electrospray ionization (ESI/MS) for studies related to environmental contamination by pesticides. The first study describes the application of a method of solid phase microextraction (SPME) with gas chromatography and mass spectrometry detector (GC/MS) for residue analysis of pesticides in water samples from the São Francisco River Basin. We studied organochlorine pesticides, organophosphates and pyrethroids. Only a few sediment samples showed the presence of residues of organochlorine pesticide endosulfan sulfate and op '-methoxychlor. The second study investigated the influence of concentration of sodium hypochlorite solution, pH and time of exposure to UV light, usually important factors on a conventional water treatment on degradation of some class of pesticides organophosphorus, organochlorine and pyrethroids. Measurements were made by SPME-GC/MS. A factorial design23 was built to determine the effects of these predominant factors, as well as the possible interactions between them. In addition, were also constructed response surfaces (through Doehlert surfaces) to assess whether the optimized conditions provide the maximum rate of degradation of eachpesticide. Later, were determinate the exposition time to UV radiation that produced complete degradation of dissulfoton and endosulfan sulfate (organophosphorus and organochlorine pesticides, respectively).Finally, the ESI/MS technique was used for monitoring the photocatalyticdegradation process of the pesticide organophosphate diazinon in aqueous medium, induced by sodium hypochlorite and ozone. With the results of this study was possible to propose a route for this pesticide degradation under such conditions. In addition to check the degradation of diazinon exposed to usual conditions of water treatment stations, the toxicity of the their products of degradation was evaluated by tests with Artemia salina